Novel Growth Hormone-Releasing Hormone Receptor Gene Mutations in Turkish Children with Isolated Growth Hormone Deficiency - ARMAN, AHMET (GALENOS YAYINCILIK, 2014)
Objective: Isolated growth hormone deficiency (IGHD) is defined as a medical condition associated with growth failure due to insufficient production of GH or lack of GH action. Mutations in the gene encoding for GH-releasing hormone receptor (GHRHR) have been detected in patients with IGHD type IB. However, genetic defects on GHRHR causing IGHD in the Turkish population have not yet been reported. To identify mutations on GHRHR gene in a population of Turkish children with IGHD. Methods: Ninety-six Turkish children with IGHD were included in this study. Exon1-13 and exon/intron boundaries of GHRHR were amplified by suitable primers. The polymerase chain reaction products for GHRHR gene were sequenced with primers. Results: We analyzed the GHRHR gene for mutations in ninety-six patients with IGHD based on sequence results. We identified novel p.K264E, p.S317T, p.S330L, p.G369V, p.T257A and C base insertion on position 380 (c.380inserC) mutations. In 5 of the patients, the mutation was homozygote and in 1-heterozygote (p.S317T). Conclusion: Six new missense mutations and one first case of insertion mutations for the GHRHR gene are reported.
Keywords: IGHD; GHRHR gene; short stature; ISOLATED GH DEFICIENCY; GHRHR GENE; SPLICE MUTATION; SHORT STATURE; PREVALENCE; POLYMORPHISM; GENERATION; SECRETION; DWARFISM; SIBLINGS